Influence of TANDUR Learning to Students's Mathematical Representation and Student Self-Concept - Maulana, Dimas Fajar; Rosita, Cita Dwi (Unnes Journal of Mathematics Education, 2017)
This study aims to determine the effect of learning model TANDUR on the ability of mathematical representation and selfconcept of students and to know the correlation between the ability of mathematical representation and selfconcept. This research is a quantitative research using an experimental method. The research design is True Experimental Design with PretestPosttest Control Group Design. The population in thisstudy is all students of class X which amounted to 350 students in one of the SMA Negeri in Cirebon city. From the population is taken the sample using simple random sampling technique as many as 60 students are divided into two groups namely groups who get TANDUR learning and groups that get conventional learning. The results showed that the TANDUR learning model had an effect of 66.9% on the selfconcept of the students, while the students' mathematical representation ability was 75.5%. Meanwhile, the correlation between selfconcept and student's mathematical representation is 74,3%.